2017
DOI: 10.1371/journal.pone.0170221
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Influence of Perceived Grasp Shape on Speech Production

Abstract: Previous research has shown that precision and power grip performance is consistently influenced by simultaneous articulation. For example, power grip responses are performed relatively fast with the open-back vowel [a], whereas precision grip responses are performed relatively fast with the close-front vowel [i]. In the present study, the participants were presented with a picture of a hand shaped to the precision or power grip. They were required to pronounce speech sounds according to the front/above perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
(73 reference statements)
2
14
0
Order By: Relevance
“…The general view is that voiced consonants might be linked to larger objects than unvoiced consonants (Newman, ; Thompson & Estes, ). Moreover, the current findings are in line with the study reported by Vainio, Rantala, et al (), which similarly did not find any influence of the viewed grip type on the pronunciation of [t] and [k], while the pronunciation of [i] and [ɑ] was significantly influenced by these stimuli. Hence, it appears that articulation processes responsible for the increasing/decreasing of the vocal cavity and lip opening for vowel production are more sensitive to influences of size‐grasp affordances than those articulation processes related to tongue shaping for consonants production.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The general view is that voiced consonants might be linked to larger objects than unvoiced consonants (Newman, ; Thompson & Estes, ). Moreover, the current findings are in line with the study reported by Vainio, Rantala, et al (), which similarly did not find any influence of the viewed grip type on the pronunciation of [t] and [k], while the pronunciation of [i] and [ɑ] was significantly influenced by these stimuli. Hence, it appears that articulation processes responsible for the increasing/decreasing of the vocal cavity and lip opening for vowel production are more sensitive to influences of size‐grasp affordances than those articulation processes related to tongue shaping for consonants production.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, this effect is in line with previous observations showing that production of the precision and power grips is planned in the motor networks that overlap with the processes related to articulation of the vowel [i] and [ɑ], respectively (Tiainen, Tiippana, et al, ; Vainio et al, ). In addition, this finding is also in line with our previous observations showing that viewing a picture of a hand shaped to the precision or power grip does not only facilitate corresponding grasp responses (Vainio, Tucker, & Ellis, ), but it can also facilitate vocal responses of the vowel [i] and [ɑ], respectively (Vainio, Rantala, et al, ). Hence, it appears that observing the precision grip or an object whose size‐grasp affordance is congruent with the precision grip can potentiate articulation of the vowel [i].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations